Controlling the Melt Resistance to Flow as a Possibility of Improving the Miscibility and the Time Behavior of Some Blends Based on Starch - Doina Dimonie; Miruna Musat; Sanda Maria Doncea; Celina Maria Damian; Liliana Anton; Eugeniu Vasile; Roxana Trusca; Maria Râpă (International Journal of Polymer Science)
The paper proves that the miscibility of some blends based on starch can be improved by finding for each of them the melt resistance to flow at which the nonstationary flow and the melt degradation are avoided and the developed shear rate homogenizes optimally the material composition. The obtained results show that, for process sensitive materials like starches, the border between good and less miscibility is so narrow that the window of melt processing conditions and the best formulation must be found for each of them. The improving of miscibility by controlling the melt resistance to flow proves to be a good method to prevent retrogradation and plasticizer leaching and so to handle the new compounds behavior during usage.